Cell scale host-pathogen modeling: another branch in the evolution of constraint-based methods - Jamshidi, Neema; Raghunathan, Anu (Frontiers in Microbiology, 2015)
Constraint-based models have become popular methods for systems biology as they enable the integration of complex, disparate datasets in a biologically cohesive framework that also supports the description of biological processes in terms of basic physicochemical constraints and relationships. The scope, scale, and application of genome scale models have grown from single cell bacteria to multi cellular interaction modeling; host-pathogen modeling represents one of these examples at the current horizon of constraint-based methods. There are now a small number of examples of host-pathogen constraint-based models in the literature, however there has not yet been a definitive description of the methodology required for the functional integration of genome scale models in order to generate simulation capable host-pathogen models. Herein we outline a systematic procedure to produce functional host-pathogen models, highlighting steps which require debugging and iterative revisions in order to successfully build a functional model. The construction of such models will enable the exploration of host-pathogen interactions by leveraging the growing wealth of omic data in order to better understand mechanism of infection and identify novel therapeutic strategies.
Keywords: constraint-based model; flux balance analysis; host-pathogen; mathematical models; omics-technologies; optimization methods; salmonella typhimurium; tuberculosis

Advances in metabolic engineering and fermentation for 3-hydroxypropionic acid biosynthesis: a comprehensive review - Joshi, Harshvardhan; Isar, Jasmine; Rangaswamy, Vidhya; Raghunathan, Anu (World Journal of Microbiology & Biotechnology, 2025)
The grand challenge in biobased Manufacturing Lies in achieving the sustainable, economically competitive conversion of renewable biomass into high-value Chemicals capable of replacing fossil-derived products. Among these, 3-hydroxypropionic acid (3-HP) has emerged as a top-tier target-an exceptionally versatile platform molecule. It finds applications in the synthesis of acrylic acid, 1,3-propanediol, and other derivatives, positioning it as a potential cornerstone for bio-based plastics. This review consolidates the latest breakthroughs in microbial 3-HP production, encompassing advanced strain engineering, pathway rewiring, cofactor optimization, metabolic modeling, and flux balance analysis. We critically examine strategies to overcome inherent metabolic and physiological constraints, including byproduct suppression, redox balancing, and tolerance engineering. Emerging approaches-such as dynamic regulation of metabolic flux, control of cell morphology and density, and integration of co-production pathways-are highlighted for their capacity to boost yields and process robustness. Additionally, we address the fermentation process innovations targeting enhanced productivity, substrate efficiency, minimal nutrient input, and industrially relevant titres. Collectively, these insights Chart a clear path toward the scalable, sustainable biomanufacturer of 3-HP.
Keywords: 1; 3-hydroxypropionaldehyde; 3-hydroxypropionic acid; 3-Propanediol; Fermentation; flux balance analysis; Metabolic engineering